Interrogating and interpreting the mediation of an emerging Australian Aboriginal social movement between 1923 and 1940. (2nd September 2016) - Burrows, Elizabeth
Abstract: The founding of the Australian Aboriginal Progressive Association (AAPA) in 1923 heralded the rise of an organized, motivated Australian Aboriginal rights movement that has continued to fight for improvements to Aboriginal people's lives. This paper investigates the media framing of this emerging movement through an analysis of print media (mainstream and alternative) coverage relating to the AAPA (1923–1930) and the Aborigines Progressive Association (1937–1940). Key questions consider how media framed each organization, their leaders and activity, who was allowed to speak, and what led to the emergence of the movement in the first place. In addition, this discussion includes an examination of how social movement and journalistic theory connect. It is argued that changes in Australia's political environment, heightened levels of oppression of Australia's Aboriginal peoples and the availability of charismatic Aboriginal leadership provided ideal conditions for the successful emergence of the Aboriginal rights movement in Australia.